Immigrants' language skills and visa category - Chiswick, B.; Lee, Y.; Miller, Paul (Wiley-Blackwell, 2006)
This article is concerned with the determinants of English language proficiency among immigrants in a longitudinal survey for Australia. It focuses on both visa category and variables derived from an economic model of the determinants of destination-language proficiency among immigrants. Skills-tested and economic immigrants have the greatest proficiency shortly after immigration, followed by family-based visa recipients, with refugees having the lowest proficiency. Other variables the same, these differences disappear by 3.5 years after immigration for speaking skills; and although they diminish, they persist longer for reading and writing skills. The variables generated from the model of destination-language proficiency (such as schooling and age at migration) are, in part, predictions of visa category, but they are more important statistically for explaining proficiency.